СУЧАСНІ РІШЕННЯ ЗАБЕЗПЕЧЕННЯ ОЦІНКИ ТА КОНТРОЛЮ БЕЗПЕКИ ПОСТАЧАННЯ ЕЛЕКТРИЧНОЇ ЕНЕРГІЇ - Pryshchepa, Yaroslav; Zamulko, Anatolii (General Energy Institute of the National Academy of Sciences of Ukraine, 2024)
The introduction of market relations in the energy industry brought the issue of energy security to a new level, defining one of its components in the market as the security of electric energy supply. In the work, a comparative analysis of the existing conceptual terminological apparatus related to the definitions of energy security and security of supply was carried out in order to establish the main differences. At the same time, assessment and control of the security of electricity supply, as integral indicators that make it possible to plan the activities of the single European energy market, have become fundamental issues for various countries. Assessment and control of the security of electricity supply in modern Ukraine is becoming an increasingly urgent task in connection with the connection of its unified energy system to the energy system of Europe and the need to ensure emergency-free parallel operation. Therefore, the purpose of the study is to form an idea of modern approaches to the assessment of the security of electricity supply in Ukraine and the EU countries, as well as to search for opportunities to improve the control system of security of supply. It was established that, apart from the prescriptive regulation of the basic principles of the formation of indicators, at the moment there are no unified approaches that would allow them to be used to create a national methodological base for a conscious and qualitative assessment of security of supply. Based on the results of the comparative analysis, the main ways by which the issue of security of supply assessment is considered have been identified. It has been proven that an important direction is the creation of a multi-level system of assessment and control of the security of electricity supply, as well as ensuring the control of the implementation of organizational measures aimed at improving the security of supply.